The politics of non-state social welfare (Ithaca, 2014)
"Across the world, welfare states are under challenge (or were never developed extensively in the first place) while non-state actors increasingly provide public goods and basic welfare. In many parts of the Middle East and South Asia, sectarian organizations and political parties supply basic services to ordinary people more extensively and effectively than governments. In sub-Saharan Africa, families struggle to pay hospital fees, and nongovernmental organizations (NGOs) launch welfare programs as states cut subsidies and social programs. Likewise, in parts of Latin America, international and domestic NGOs and, increasingly, private firms are key suppliers of social welfare in both urban and rural communities. Even in the United States, where the welfare state is far more developed, secular NGOs and faith-based organizations are critical components of social safety nets. Despite official entitlements to public welfare, citizens in Russia face increasing out-of-pocket expenses as they are effectively compelled to seek social services through the private market.